2006
DOI: 10.1111/j.1365-2125.2006.02656.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and systemic endocrine effects of the phyto‐oestrogen 8‐prenylnaringenin after single oral doses to postmenopausal women

Abstract: AimsPre-clinical data suggest that the racemic phyto-oestrogen 8-prenylnaringenin (8-PN) may have beneficial effects in postmenopausal women and may become an alternative to classical hormone replacement therapy (HRT) treatment regimes. The aim of this study was to investigate the pharmacokinetics, endocrine effects and tolerability of chemically synthesized 8-PN in postmenopausal women. MethodsThe study was performed using a randomized, double-blind, placebo-controlled, doseescalation design with three groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
92
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 29 publications
(33 reference statements)
6
92
0
2
Order By: Relevance
“…It could be demonstrated that daily intake over 12 weeks of a hop extract, standardized on 250 mg 8-PN, exerted favorable effects on vasomotor symptoms and other menopausal discomforts (Heyerick et al 2006). Consistent with these findings, Rad et al (2006) reported that a single dose of 750 mg 8-PN reduced LH serum levels in postmenopausal women. Interestingly, it appeared from these experiments that 8-PN was well tolerated by these women.…”
Section: Introductionsupporting
confidence: 78%
“…It could be demonstrated that daily intake over 12 weeks of a hop extract, standardized on 250 mg 8-PN, exerted favorable effects on vasomotor symptoms and other menopausal discomforts (Heyerick et al 2006). Consistent with these findings, Rad et al (2006) reported that a single dose of 750 mg 8-PN reduced LH serum levels in postmenopausal women. Interestingly, it appeared from these experiments that 8-PN was well tolerated by these women.…”
Section: Introductionsupporting
confidence: 78%
“…6-DMAN, although possessing a different substituent, fits nicely Page 13 of 29 A c c e p t e d M a n u s c r i p t within this range. Some authors suggest that 8-PN may have beneficial effects in postmenopausal women and may become an alternative to classical HRT treatment regimes (Rad et al, 2006). Our data indicate that 6-DMAN with its lack of uterine stimulation might match the criteria for HRT much better than the pure E2 agonist 8-PN, because it lacks the proliferational effect on the endometrial cells which may increase the risk of formation of endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 68%
“…Recently, 8-PN was tested in animals [26,27] and in a human phase I clinical trial [28]. While H. lupulus extracts have also been tested in two phase I clinical trials in menopausal women [29], extracts have not been rigorously tested in vivo following the identification of 8-PN as the compound primarily responsible for estrogenic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugates of 8-PN were also reported in urine of men after consuming beer or beer spiked with 8-PN [25], but the radioimmunoassay used in this study did not allow for the identification of specific conjugates. However, little information is available concerning the formation of metabolites of 8-PN in vivo.Recently, 8-PN was tested in animals [26,27] and in a human phase I clinical trial [28]. While H. lupulus extracts have also been tested in two phase I clinical trials in menopausal women [29], extracts have not been rigorously tested in vivo following the identification of 8-PN as the compound primarily responsible for estrogenic activity.…”
mentioning
confidence: 99%